Marketing strategy for start-up company Didogo group in CEE region with focus on new media and communications - Shubik, Elena (2011)
This master thesis focuses on e-commerce, online marketing and Social Media marketing potential from theoretical factual and practical perspective. On the example of real start-up e-shop Didogo Group Ltd. it aims to show various possibilities how to enhance the company's and brands' recognition while implementing various online marketing and advertising tools. Particular focus is put on Social Media as up to date platforms suitable for marketing and advertising usage. After providing general theoretical and factual overview of e-commerce in the world as well as in Czech Republic, detailed description of various internet marketing tools and Social Media, it analysis Didogo's current state and marketing tools used up to date, and further provides list of recommendations for future marketing communication strategy of this company. Master thesis contains 79 pages, 10 figures, and 7 Appendixes.